Distribution of doctors’ workforce in Erbil Governorate - Wahab, Moayad A.; Husein, Vian M.; Al-Hadithi, Tariq S. (Zanco Journal of Medical Sciences (ZJMS), 2016)
<p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Background and objective: Imbalance in the distribution of health workforce might result in inequities in health services delivery. The aim of this study was to assess the distribution of doctors’ workforce in Erbil governorate and identify the possible reasons for rapid turnover of doctors. <p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Methods: This descriptive cross-sectional study included all the 962 doctors working in the health facilities of Erbil governorate. A questionnaire was used to collect data that included 40 questions divided into four broad sections of identification information, socio-demographic characteristics, information on professional characteristics and factors influencing employment process in rural areas. <p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Results: There were 5.1 doctors per 10,000 populations. Most of the doctors were deployed in urban areas (83.6%). Most doctors were working in hospitals (74.2%) and 23.3% in primary health centers. Specialists constituted the largest categories of doctors (33.5%) and general practitioners the smallest (6.7%). Doctors’ willingness to stay at the current workplace was significantly associated with being married, having opportunities to select workplace, working in private clinics and having the workplace inside Erbil. <p style="color: #000000; font-family: Tahoma; font-size: large; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #fff7f3; text-align: justify;">Conclusion: The density of doctors per 10,000 populations in Erbil governorate is below the regional and international average, with a remarkable urban-rural imbalance in numerical, geographical and institutional terms.